2013
DOI: 10.1167/iovs.13-12617
|View full text |Cite
|
Sign up to set email alerts
|

Intrasession Test–Retest Variability of Microperimetry in Age-Related Macular Degeneration

Abstract: A significant increase in sensitivity between the first and second test, but not in the subsequent tests, was found for participants who had not performed microperimetry previously. Intrasession test-retest variability can therefore be minimized by discarding the first examination to avoid the influence of a learning effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
123
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(147 citation statements)
references
References 28 publications
20
123
4
Order By: Relevance
“…24 We had expected that given the short duration of each test, participants would have required a greater number of examinations before becoming familiarized with this test and, thus, exhibit a learning effect over several examinations. Instead, we did not find a significant intrasession learning effect and, therefore, these measurements could be used to compare to those obtained by microperimetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 We had expected that given the short duration of each test, participants would have required a greater number of examinations before becoming familiarized with this test and, thus, exhibit a learning effect over several examinations. Instead, we did not find a significant intrasession learning effect and, therefore, these measurements could be used to compare to those obtained by microperimetry.…”
Section: Discussionmentioning
confidence: 99%
“…24 In short, the MAIA microperimeter performs fundus-tracking using a line scanning laser ophthalmoscope that illuminates the fundus using a superluminescent diode with a central wavelength of 850 nm, using the entire fundus as a reference for fundus tracking at 25 frames per second. A red circle 18 in diameter was used as a fixation target, and Goldman III sized stimuli were presented against a background of 1.27 cd/m 2 using a 4-2 staircase threshold strategy.…”
Section: Microperimetric Examinationmentioning
confidence: 99%
“…As shown in earlier studies, automatic fundus perimetry and the first microperimetry that uses a true eye-tracking system (MP1) allow accurate, repeatable, and topographically specific examination of retinal sensitivity [4,[7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 98%
“…These results strongly suggest that there is no learning effect of retinal average sensitivity and macular integrity by using MAIA microperimetry. In the literature, Wu et al [11] showed a significant learning effect on mean sensitivity between the first and the second test sections in AMD patients with MP1 microperimetry. In contrast, Wong et al [15] demonstrated no learning effect on the mean sensitivity in glaucoma patients by using MAIA microperimetry.…”
Section: Discussionmentioning
confidence: 99%
“…Test durations for both standard and reduced mesopic conditions were approximately 10 minutes after a practise test was completed to avoid the influence of a learning effect (Wu, Ayton, Guymer & Luu 2013). …”
Section: Microperimetrymentioning
confidence: 99%